PENDEKATAN DALAM PROSES BELAJAR: KAJIAN KITAB AYYUH? AL-WALAD: KAJIAN KITAB AYYUH? AL-WALAD - Mudhoffar (JURNAL PUSAKA, 2018)
Learning is a very essential human need. Learning can develop human potency, both physical and spiritual. Learning is also an obligation that must be done by every human being. Approach in the learning process is needed so that students can get useful knowledge. From this background the writer will discuss it in an article entitled "Approach in the Learning Process: A Study of the book Ayyuh? al-Walad”. In this essay, the author tries to analyze al-Ghaz?l?'s thinking as the main reference material, arguing that al-Ghaz?l? is well-known as a very influential figure in Islamic education. From the discussion, it can be conveyed that the approach in the learning process to obtain useful knowledge, according Al-Ghaz?l?’s Ayyuh? al-Walad, is an approach that is full of divine nuances. This is evidenced by his view that valuable learning is if it for the sake of getting closer to God, motivation in learning must be in order to revive the Prophet's Shari'ah and subdue lust, students must maintain the sanctity of their souls, and students must practice the knowledge they obtain. The factors that determine success in the learning process of Imam al-Ghaz?l?'s perspective in the book Ayyuh? al-Walad are motivational factors, educators, curriculum, student attitudes, heart purity, and social environment.